Flap Versus Tunneling for Horizontal Ridge Augmentation With FDBA and i‐ PRF : A Randomized Controlled Clinical Trial - Maryam Heidaryzadeh; Mohammad Mohammadi; Nazila Lashkarizadeh; Mahsa Kalantari Khandani (Clinical Implant Dentistry and Related Research, 2026)
ABSTRACT Aim This study evaluated the efficacy of conventional flap and tunneling techniques for horizontal alveolar ridge augmentation using freeze‐dried bone allograft (FDBA) particles combined with injectable platelet‐rich fibrin (i‐PRF). Materials and Methods Forty‐five patients were randomly allocated to one of three groups ( n = 15 each): conventional flap (CF), tunneling with membrane (TM), or tunneling without membrane (TnM). Preoperative ridge width was measured via cone beam computed tomography (CBCT). All augmentation procedures incorporated FDBA and i‐PRF; an absorbable collagen membrane was applied in the CF and TM groups. Follow‐up assessments, including CBCT imaging and histomorphometric analysis, were conducted 6 months postoperatively. For normally distributed data, ANOVA with Tukey's post hoc test and paired samples t ‐test were applied. Non‐normally distributed data were analyzed using Kruskal‐Wallis, Mann–Whitney U , and Wilcoxon signed‐rank tests. Results Statistical analysis was performed on 43 patients. All groups demonstrated an increase in ridge width after 6 months. At the 2 mm level, the mean width gain was 1.28 mm (95% CI: 0.17 to 2.40) in the TM group, 2.85 mm (95% CI: 1.80 to 3.89) in the TnM group, and 1.95 mm (95% CI: 1.07 to 2.83) in the CF group. However, statistical analysis revealed no significant intergroup variation ( p > 0.05). Histomorphometric assessments similarly demonstrated comparable outcomes across all groups, with no statistically significant differences observed ( p > 0.05). Conclusion Within the limitations of this study, the tunneling technique, regardless of membrane use, appears to be a clinically viable alternative to the conventional flap method for horizontal alveolar ridge augmentation. However, further studies with longer follow‐up periods are required to substantiate these findings. Trial Registration: irct.behdasht.gov.ir identifier: IRCT 20101204005305N21